1992
DOI: 10.1016/0090-1229(92)90036-n
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor necrosis factor in sepsis

Abstract: There is an increasing incidence of sepsis among hospitalized patients. Also, high mortality associated with sepsis and septic shock persists despite appropriate antibiotic therapy. Recent investigations have demonstrated that bacterial antigens stimulate a cascade of cellular mediators or cytokine release. In sepsis and septic shock the response of these cytokines often exceeds natural downregulation and leads to multisystem organ failure and even death in an unacceptably high number of patients. Many investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 37 publications
0
66
0
4
Order By: Relevance
“…Cytokines such as GM-CSF and interferon-gamma (IFN-gamma) have synergistic actions within this system. The observation that inhibiting the formation or the activity of TNF-alpha and/or IL-1 led to a reduction of endotoxin-or (Gram-negative) bacteria-induced sepsis mortality in different animal models underlined the role of this cytokine in the pathogenesis of sepsis and septic shock [3][4][5][6][7][8]. Studies on genetically manipulated mice with defined genetic deficiencies ("knock-out" mice) corroborated these findings.…”
Section: Sepsis -The Failure Of the Anti-inflammatory Therapeutic Strmentioning
confidence: 67%
“…Cytokines such as GM-CSF and interferon-gamma (IFN-gamma) have synergistic actions within this system. The observation that inhibiting the formation or the activity of TNF-alpha and/or IL-1 led to a reduction of endotoxin-or (Gram-negative) bacteria-induced sepsis mortality in different animal models underlined the role of this cytokine in the pathogenesis of sepsis and septic shock [3][4][5][6][7][8]. Studies on genetically manipulated mice with defined genetic deficiencies ("knock-out" mice) corroborated these findings.…”
Section: Sepsis -The Failure Of the Anti-inflammatory Therapeutic Strmentioning
confidence: 67%
“…IL-1ÎČ enhances the recruitment of inflammatory cells into airspaces and alters vascular permeability, leading to fluid transport and subsequent lung edema formation (Pugin et al 1996;Olman et al 2002). Because IL-6 is mainly produced in the lung, the level of IL-6 is a good index to assess the early injury of the lung (Spooner et al 1992). A study by Gultekin et al (2007) showed that leptin treatment ameliorated acute lung injury in rats by decreasing the production of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Septic shock is induced by bacterial release of endotoxins, which trigger intense production of proinflammatory cytokines, such as TNF-␣ that ultimately lead to multiorgan failure, including liver destruction. 9 We showed (Fig. 2B) that TNFR1⌬DD inhibited TNF-␣-dependent apoptosis of HeLa cells.…”
Section: Membrane-anchored Tnfr1 Decoys Protect Micementioning
confidence: 97%